Peran Media Pembelajaran Dalam Pendidikan Berdasarkan Kajian Sutta Pitaka - Joko Adi Pradana; Julia Surya; Sakawana Sakawana; Bayu Wiradharma; Mai Triana (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This article discusses the role of media in conveying information and learning in the context of technological developments, especially artificial intelligence (AI), as well as implementing it towards understanding spiritual teachings from religious literature, especially the Sutta Pitaka. The research uses qualitative and hermeneutic methods to analyze the concept of learning media in the Suttapiṭaka and its application in Buddha's life. In his Sutta studies, the Buddha used various imagery and visual devices to teach the Dhamma, making understanding easier for students. Learning media, such as in the story of Bhikkhu Culapanthaka, have an important role in facilitating understanding of complex concepts. However, the development of AI raises pros and cons regarding its use in education, with some concerns regarding dependency and lack of discipline. Nevertheless, the great potential of AI in the world of education must be developed wisely by educators. The importance of using appropriate learning media in the educational context is emphasized, along with the emphasis on active, innovative and creative learning paradigms. In conclusion, learning media plays an integral role in learning, while the use of AI in education has great opportunities but must be implemented with careful consideration by educators.